When Can Women Close the Gap? A Meta-Analytic Test of Sex Differences in Performance and Rewards - Joshi, Aparna; Son, Jooyeon; Roh, Hyuntak (Academy of Management Journal, 2015)
Drawing on macro and micro domains in gender research, we meta-analytically test whether occupation-, industry-, and job-level factors mitigate or exacerbate differences in performance evaluations (k = 93; n = 95,882) and rewards (k = 97; n = 378,850) between men and women. Based on studies conducted across a variety of work settings and spanning nearly 30 years, we found that the sex differences in rewards (d = .56) (including salary, bonuses, and promotions) were 14 times larger than sex differences in performance evaluations (d = .04), and that differences in performance evaluations did not explain reward differences between men and women. The percentage of men in an occupation and the complexity of jobs performed by employees enhanced the male–female gap in performance and rewards. In highly prestigious occupations, women performed equally, but were rewarded significantly lower than men. Only a higher representation of female executives at the industry level enabled women to reverse the gender gap in rewards and performance evaluations. Our configurational analysis also revealed that some occupation-, industry-, and job-level attributes of the work context jointly contributed to differences in rewards and performance evaluations.